2018
DOI: 10.4103/0366-6999.244107
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Dynesys Dynamic Stabilization for Lumbar Spinal Stenosis

Abstract: Background:Many clinical studies over the past decade have indicated positive outcomes for patients treated with Dynesys dynamic stabilization for lumbar degenerative disease. However, long-term outcomes of Dynesys for lumbar spinal stenosis are rarely reported. The aim of this study was to analyze the long-term clinical and radiologic outcomes for patients with lumbar spinal stenosis treated with Dynesys stabilization.Methods:Thirty-eight patients with lumbar spinal stenosis were treated with Dynesys stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Under flexion-extension, lateral bending, and axial torsion conditions, the total ROM and the ROM of surgical segment in the surgery-simulation models decreased to some extent in the present study, but the BioFlex system showed a more decrease compared to Dynesys system. This result is similar with the results from some study [15][16][17]. Our study showed an encouraging result in that the Dynesys system model had the closest ROM to the intact group.…”
Section: Discussionsupporting
confidence: 92%
“…Under flexion-extension, lateral bending, and axial torsion conditions, the total ROM and the ROM of surgical segment in the surgery-simulation models decreased to some extent in the present study, but the BioFlex system showed a more decrease compared to Dynesys system. This result is similar with the results from some study [15][16][17]. Our study showed an encouraging result in that the Dynesys system model had the closest ROM to the intact group.…”
Section: Discussionsupporting
confidence: 92%
“…1,2 However, instrumented fusion causes complications, including instrumentation failure, pseudoarthrosis, and pain in donor areas. [3][4][5] Moreover, the preservation of lumbar motion is less considered in fusion instrument, leading to the limited motility of stabilized segments and the increased load on adjacent segments, which may increase the risk of adjacent segment degeneration (ASDeg), adjacent segment disease (ASDis), and severe postoperative functional disabilities. [6][7][8] In recent years, non-fusion systems have been applied clinically to prevent the incidence of adjacent segment pathology (ASP, including ASDeg and ASDis) after lumbar surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…11 This system consists of pedicle screws (Ti alloy), polyethylene-terephtalate (PET) cords, and polycarbonate-urethane (PCU) spacers for stabilization of stabilized segments, restoration of normal segmental kinematics, and preservation of adjacent motion to prevent the instability and decrease the incidence of ASP. 5,[12][13][14] Many studies reported that the Dynesys system (DS) showed signi cant improvement in terms of visual analog scale (VAS) pain scores, Oswestry disability index (ODI) scores, trauma severity, and recovery time than fusion method. 4,[15][16][17][18][19] Moreover, the range of movement (ROM) at adjacent segments and along with the load across the intervertebral and adjacent discs was reduced.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations